Grain orientation evolution and thermoelectric properties of textured (Ca0.87Ag0.1La0.03)3Co4O9 ceramics prepared by tape casting. Issue 6 (15th March 2021) - Shi, Zongmo; Zhang, Ping; Lou, Zhihao; Qin, Mengjie; Xu, Jie; Yan, Haixue; Gao, Feng
Abstract: (Ca0.87 Ag0.1 La0.03 )3 Co4 O9 ceramics along [00 l ]c crystallographic orientation were prepared by using tape casting combined with template grain growth method, which were regulated bywhich the sintering temperature and the soaking time. The (La, Ag) co-doping not only can balance the contradiction of the electrical resistivity and Seebeck coefficient, but also generat the point-defects to increase phonon scattering, which can lower thermal conductivity. The effect of grain orientation evolution on thermoelectric properties was investigated and the mechanism of epitaxial growth was discussed through the analysis of microstructures. The results show that the optimized sintering parameters led to great changes in the degree of texturing, which was closely related to thermoelectric performance. A large Seebeck coefficient of 232 μV/K was obtained for the 40 h sample and the high Lotgering factor of 92.7% for the 20 h sample reached, giving rise to the power factor of 0.38 mW/(m·K 2 ) at 1073 K. The morphologic orientation and epitaxial growth give a possible route of preparing highly textured ceramics and achieving high thermoelectric properties.